Self-Compassion for Improving Flow and Reducing Music Performance Anxiety: A Preliminary Mixed Methods Investigation of Musicians’ Performance Experiences - Wu, Di (Université d'Ottawa | University of Ottawa, 2024)
The competitive demands of public performances significantly impact musicians’ performance experiences within the traditional music education framework. Aiming to investigate the mediating role of self-compassion in enhancing music performance experiences, I explored 35 Chinese university students’ flow and music performance anxiety (MPA), two antithetical constructs that influence performance experiences positively or negatively. Instead of focusing on performance outcomes, this interdisciplinary study examined participants’ flow, MPA, and self-compassion before and after they undertook either the Performance Strategies Class (PSC) or the Mindful Self-Compassion (MSC) program delivered by professional trainers. Employing mixed methods convergent design, I used questionnaires to assess trait measures (flow, MPA, and self-compassion) and collected data on state measures (flow and MPA) during public performance settings, where participants performed piano solo pieces by memory. Participants also provided qualitative written responses reflecting their self-perceived changes in their two live performance experiences. Mixed-design Analyses of Variance (ANOVAs) showed significant improvements in all participants’ performance experiences from pre- to post-training. Compared to the PSC program, the MSC program significantly improved participants’ state flow and trait self-compassion. The MSC program also significantly outperformed the PSC program in reducing participants’ trait and state MPA. Using reflexive thematic analysis, I identified key themes that corroborated the quantitative results. The mixed methods findings showed positive outcomes in both programs and demonstrated the superior effectiveness of the MSC program in improving flow and reducing MPA. These findings suggest that integrating self-compassion training into music performance strategies can effectively enhance musicians’ overall positive performance experiences by reducing MPA and improving flow.
Keywords: music performance; self-compassion; flow; performance anxiety; positive performance experiences; Mindful Self-Compassion; mixed methods